Pedagogical Competence of Teachers at Pasundan 1 Senior High School Bandung in the Academic Year 2021–2022 - Rakhman, Muhammad Arief; Marisa, Harni (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
This study examines the impact of pedagogical competence, educational infrastructure, and non-physical work environment on the performance of teachers at SMA Pasundan 1 Bandung. The research aims to identify the extent to which these factors contribute to enhancing teacher performance, which is crucial for improving educational outcomes. The findings reveal that pedagogical competence has a strong positive correlation with educational infrastructure, and both factors significantly influence the non-physical work environment. Furthermore, the study highlights the importance of continuous professional development and the adaptation of innovative teaching methods, especially in the transition to hybrid learning in the new normal era. The study concludes with recommendations for school administrators to prioritize the improvement of these critical areas to foster a more effective and conducive teaching environment.